Family Nursing Care for Gout Arthritis Patients Using Soursop Juice as a Non-Pharmacological Therapy to Reduce Uric Acid Levels - Asep Gunawan; Deuis Diana Sari; Rudi Kurniawan (Jurnal Vocational Nursing Sciences (VNUS), 2025)
Gout arthritis is a form of joint inflammation caused by the accumulation of urate crystals, resulting in pain, swelling, and limited mobility. Non-pharmacological therapy such as soursop (Annona muricata) juice, which contains antioxidants and xanthine oxidase inhibitors, may help reduce uric acid levels. This case study was conducted on Mr. A, a patient with gout arthritis living in Palasari Hamlet, Sukahurip Village, Ciamis. The intervention consisted of daily soursop juice administration for five consecutive days, with monitoring of uric acid levels and pain symptoms. After treatment, uric acid decreased slightly from 8.7 mg/dL to 8.6 mg/dL, accompanied by reduced pain and swelling. Although the reduction was minimal, soursop juice showed potential as a safe, low-cost complementary therapy for gout arthritis management in family settings.